Kelompok Sempalan: Sisi Lain Dinamika Politik Kita - Idrus, Muhammad (Unisia, 2016)
The arising of illegal political groups relatively represent the Indonesian leadership patterns. In ORBA, these groups emerge as the manifestation of the twarthened politic communication and of the oppresive policy in finding the conflict solutions. There are many various kinds of illegal political groups that generally can be assimilated as reaction toward the unsolved crisis and ofimbalance development policies that destroy the human values. As a response to the illegal politic groups whose emergences are identified as violence movements, the government should make any systematical improvements. One of them-according to the writer of this book-should be conducted by maintaining the democracy in Indonesia.